RANCANG BANGUN RANGKA MESIN PERAJANG SINGKONG DENGAN TENAGA MOTOR ¼ HP KAPASITAS 30 KG/JAM - Pabesak, Alexander Fajar; Saleh, Agus (Jurnal Mahasiswa Terapan, 2024)
Development of technology, especially in MSMEs, there is a demand to create a tool that has the ability to reduce the risk of injury when chopping cassava and streamline the chopping process time. A cassava chopping machine is a machine that has a knife with sharp edges for cutting. This cassava chopping machine has a rotating mechanism, so it can cut cassava to a size that has been adjusted for thickness. The design of the cassava chopping machine frame with the following specifications: machine dimensions 525mm x 330mm x 300mm with 220V motor power is intended to be able to overcome cassava production problems. The frame is an important element that cannot be separated in the design and manufacture of a machine. The material used to make the cassava chopping machine frame is angle iron with dimensions of 30 x 30 x 3 mm and the type of material used is low carbon steel. The design and manufacture of the cassava chopping machine frame includes 4 main stages: cutting, joining, drilling, finishing.